Occupation and bladder cancer in european women - Mannetje, Andrea 't; Chang-Claude, Jenny; Wahrendorf, Jürgen (Cancer causes & control, 1999)
Objectives: We examined the importance of occupational exposures for bladder cancer in women. Methods: We combined data from 11 case-control studies conducted between 1976 and 1996 in six European countries. The pooled data comprised 700 incident female cases and 2425 population or hospital controls, aged 30-79 years. Lifetime occupational and smoking history were examined using common coding. Results: Excess risks were found in only a few of the occupations previously identified at high risk for bladder cancer. Statistically significant excess risks were observed for metal workers, particularly blacksmiths, toolmakers and machine tool operators (OR: 2.0, 95% CI: 1.1-3.6), tobacco workers (OR: 3.1, 95% CI: 1.1-9.3), field crop and vegetable farm workers (OR: 1.8, 95% CI: 1.0-3.1), tailors and dress makers (OR: 1.4, 95% CI: 1.0-2.1), saleswomen (OR: 2.6, 95% CI: 1.0-6.9), and mail sorting clerks (OR: 4.4, 95% CI: 1.0-19.5). About 8% (95% CI: 3.1-19.9) of all bladder cancers in women could be attributed to occupation after adjusting for smoking. The attributable risk was higher in women aged less than 65 years (12%), compared to older women (4%). Conclusions: The calculation of the attributable risk on the basis of results from this analysis may have caused some overestimation of the proportion of occupational bladder cancer in women. A significant proportion, however, of bladder cancer cases among European women less than 65 years is likely to be attributed to occupation. This link between bladder cancer in women and occupational factors has received little recognition, probably because studies addressing these issues have predominantly been done in men.